Peningkatan kualitas layanan perpustakaan dan pengelolaan koleksi di Politeknik Pariwisata NHI Bandung - Lina Rismawati (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
University libraries are crucial for the implementation of the Tri Dharma of Higher Education. Complex user needs demand efficient services and reliable collection management. This community service program took place at the NHI Bandung Tourism Polytechnic Library over 40 working days, using a participatory approach and fostering close collaboration between the team and librarians. Activities focused on supporting thesis/final project (TA/PA) services, digital and print collection processing, archive handling, and security checks. Results showed a more organized TA/PA workflow and controlled access to TA/PA collections over the past 6 years (2019–2024). Digital discovery improved with the addition of Emerald e-journal metadata to the library website, and new printed books were thoroughly processed (classification, cataloging, labeling, and shelving). Collection governance was strengthened through the weeding of 612 items and a physical inventory of 14,479 items, supported by sensory checks of reference materials. These results demonstrate that targeted operational support can improve service efficiency, data accuracy, and collection relevance; Libraries must standardize workflows, schedule regular weeding/inventories, and modernize supporting equipment. The next step is to measure user satisfaction and match the physical collection with the integrated catalog.